PEMELIHARAAN DAN KESIAPAN PESAWAT G 120TP-A GROB DI LANUD ADISUTJIPTO - Ainul Chuzam; Bambang Kustiawan; Marsono Marsono (Universitas Perrtahanan Indonesia (UNHAN), 2023)
The main task of the Adisutjipto Air Base is to organize aerospace education, training and development. Maintenance, readiness and allocation of aircraft flight hours are important tasks. The objectives of this study were 1) to analyse the factual conditions of the maintenance process, readiness and flight hours for the G 120 TP-A Grob aircraft and 2) to analyse the dominant factors affecting the maintenance process. This research is a descriptive study with a qualitative approach supported by quantitative data. Quantitative methods in this study were used to see the most influential factors on maintenance. Methods of data collection using questionnaires, interviews and documentation. The results of the study show 1) there is an inaccuracy in the medium-level maintenance planning process that it affects the results of the calculation of the percentage of maintenance and maintenance of light and heavy levels that have not been included in the calculation, 2) the dominant factor affecting the results of maintenance is HR on quantity indicators and maintenance support factors, especially indicators of needs partsPEMELIHARAAN DAN KESIAPAN PESAWAT G 120TP-A GROB DI LANUD ADISUTJIPTO